Factors associated with caffeine intake among undergraduates: a cross-sectional study from Palestine - May Hamdan; Souzan Zidan; Fatima Al-Amouri; Hiba Niroukh; Manar Abu Dawod; Sajeda Ashour; Shahd Sameer Dweik; Manal Badrasawi (Journal of Health, Population and Nutrition)
Abstract Background Caffeine is one of the world’s most frequently consumed central nervous system stimulants. Moderate caffeine intake has beneficial health effects, while increased caffeine intake may have harmful effects in the human body. Existing literature indicated that undergraduates consume caffeine excessively. Till this date, little is known about the consumption pattern of caffeine among Palestinian undergraduates. Therefore, the current study aimed to estimate the percentage of caffeine consumption among Palestinian undergraduates, to assess their caffeine daily intake, and to identify factors associated with unsafe caffeine consumption. Methods A cross-sectional study was conducted in Palestine between March and May 2022. Undergraduates were recruited by random sampling after a personal invitation. Undergraduates aged between 18 and 25 were included in the study, while those who were taking medications, had medical conditions affecting the data collection process, and had incomplete responses were excluded from the study. Caffeine consumption was assessed using a semi-quantitative food frequency questionnaire (FFQ) developed by the research team. The content validity of the FFQ was done by three reviewers. Also, a questionnaire was used to collect data related to sociodemographic characteristics, medical history, lifestyle habits, sleeping quality, physical activity, and psychological status. Data were analyzed through the descriptive statistics and inferential statistics (Chi-square test, Mann-Whitney test, and Kruskal-Wallis H test). Results The final analysis included 486 undergraduates with a mean age of 20.1 ± 1.48 years. The majority of the undergraduates were female (65.0%) and single (89.5%). The sample was distributed almost equally between the first (26.3%), second (23.0%), third (22.8%), and fourth (18.7%) academic years, and only 44 undergraduates (9.1%) were in their fifth year. The vast majority of university students (96.5%) consumed caffeinated products, with coffee ranking first place. Nearly half of the participants (32.7%) exceeded the safe levels of caffeine consumption. Males, smokers, poor physical activity, higher Sleep Hygiene Index (SHI) scores, and greater anxiety, stress, and depression scores had significantly higher rates of unsafe caffeine intake than their peers (p < 0.05). The total caffeine consumption was significantly associated with gender, low household income, smoking status, physical activity level, SHI score, as well as anxiety (p < 0.05). Conclusion Caffeine consumption in the studied sample was significantly high and exceeded the safe levels. The current study revealed that unsafe caffeine consumption was more common among males, smokers, and physically active individuals. Caffeine intake was also linked to poor-quality sleep and higher psychological concerns. Therefore, educational programs are recommended to increase awareness of the adverse effects of high caffeine intake.